2012
DOI: 10.1002/pro.2052
|View full text |Cite
|
Sign up to set email alerts
|

Ratcheting up protein translocation with anthrax toxin

Abstract: Energy-consuming nanomachines catalyze the directed movement of biopolymers in the cell. They are found both dissolved in the aqueous cytosol as well as embedded in lipid bilayers. Inquiries into the molecular mechanism of nanomachine-catalyzed biopolymer transport have revealed that these machines are equipped with molecular parts, including adjustable clamps, levers, and adaptors, which interact favorably with substrate polypeptides. Biological nanomachines that catalyze protein transport, known as transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 118 publications
4
86
0
Order By: Relevance
“…One model suggests that LF and EF thread through the pore. 19,20 The results shown here suggest that anthrax toxin complexes (i.e., LF or EF bound to the PA 63 channel) rupture membranes. A previous study demonstrated that LF in the complex is enzymatically active.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…One model suggests that LF and EF thread through the pore. 19,20 The results shown here suggest that anthrax toxin complexes (i.e., LF or EF bound to the PA 63 channel) rupture membranes. A previous study demonstrated that LF in the complex is enzymatically active.…”
Section: Introductionmentioning
confidence: 78%
“…Several groups hypothesized that the transport of LF and EF into the cell requires their translocation through the PA 63 pore, 19,20 which has a diameter of ≈1.2-2 nm. [21][22][23] Previous electrophysiological studies demonstrated that full-length LF and EF (≈760 amino acids each) [24][25][26][27] fragments (LF N and EF N , ≈254 amino acids each) [28][29][30][31][32] bind strongly but reversibly to the channel and reduce the pore conductance.…”
Section: Introductionmentioning
confidence: 99%
“…These pores act as translocons, which unfold LF and EF and transport them across the endosomal membrane to the cytosol (see latest review). 1 Prior to structural verification, biochemical and biophysical data indicated that domain 2 (residues 259-487) of the PA prepore rearranges to form a 100 Å -long beta barrel that connects the globular portion of the PA to the target membrane, forming a transmembrane pore. The overall shape of the translocon has been validated using both 2D and ultimately 3D electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Anthrax toxin (Atx) (13,14)-a virulence factor produced by pathogenic strains of Bacillus anthracis-consists of three nontoxic protein components. The protective antigen (PA) component (83 kDa) binds to cells and forms an oligomeric translocase channel, allowing the other two enzyme components, lethal factor (LF; 90 kDa) and edema factor (EF; 89 kDa), to translocate into the host cell.…”
mentioning
confidence: 99%